Regional variation in breast cancer treatment in the Netherlands and the role of external peer review: a cohort study comprising 63,516 women - Kilsdonk, Melvin J (BioMed Central, 2014)
BACKGROUND: Treatment variation is an important issue in health care provision. An external peer review programme for multidisciplinary cancer care was introduced in 1994 in the Netherlands to improve the multidisciplinary organisation of cancer care in hospitals. So far the clinical impact of external quality assessment programmes such as external peer review and accreditation remains unclear. Our objective was to examine the degree of variation in treatment patterns and the possible effect of external peer review for multidisciplinary cancer care for breast cancer patients. METHODS: Patients with breast cancer were included from 23 hospitals from two ‘intervention regions’ with the longest experience with the programme and 7 hospitals that never participated (control group). Data on tumour and treatment characteristics were retrieved from the Netherlands Cancer Registry. Treatment modalities investigated were: the completeness of breast conserving therapy, introduction of the sentinel node biopsy, radiotherapy after breast conserving surgery for ductal carcinoma in situ (DCIS), adjuvant radiotherapy for locally advanced breast cancer (T3/M0 or any T,N2-3/M0), adjuvant chemotherapy for early stage breast cancer (T1-2/N+/M0) and neo-adjuvant chemotherapy for T4/M0 breast cancer. Hospitals from the two intervention regions were dichotomised based on their implementation proportion (IP) of recommendations from the final reports of each peer review (high IP vs. low IP). This was regarded as a measure of how well a hospital participated in the programme. RESULTS: 63,516 female breast cancer patients were included (1990-2010). Variation in treatment patterns was observed between the intervention regions and control group. Multidisciplinary treatment patterns were not consistently better for patients from hospitals with a high IP. CONCLUSIONS: There is no relationship between the external peer review programme for multidisciplinary cancer care and multidisciplinary treatment patterns for breast cancer patients. Regional factors seem to exert a stronger effect on treatment patterns than hospital participation in external peer review. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2407-14-596) contains supplementary material, which is available to authorized users.